2021
DOI: 10.1021/acs.jpca.1c00255
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer in Nitromethane–Ammonia Clusters under VUV Single-Photon Ionization Explored by Infrared Spectroscopy and Theoretical Calculations

Abstract: It is known that the acidity and reactivity of the CH bond can be enhanced after ionization. Also, this property plays a pivotal role in proton transfer reaction and in the formation of new molecules. Herein, infrared spectroscopy and high-precision quantum chemical calculations are used to study the neutral and cationic clusters of nitromethane−ammonia (CH 3 NO 2 -NH 3 ). It is found that in the neutral cluster, CH 3 NO 2 and NH 3 are mainly bonded by three intermolecular hydrogen bonds, in which electrostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…The IR laser beam was focused on the ionization region using a CaF 2 lens with a 200 mm focal length, in which the direction of the IR beam was counter-propagating with the VUV beam. 40,41…”
Section: Methodsmentioning
confidence: 99%
“…The IR laser beam was focused on the ionization region using a CaF 2 lens with a 200 mm focal length, in which the direction of the IR beam was counter-propagating with the VUV beam. 40,41…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated that the acidities of CH bonds in ionized alkanes, 33 alcohols, 34 and ethers 35 remarkably increase due to the hyperconjugation effect. Consequently, proton transfer reactions often proceed readily in ion−molecule reactions involving relevant clusters, like those between pentane and water, 36 nitromethane and ammonia, 37 trimethylamine dimer, 38 etc.…”
Section: Introductionmentioning
confidence: 99%